Li+ doped anodic TiO2 nanotubes for enhanced efficiency of Dye-sensitized solar cells - Cha, Gi; Özkan, Selda; Hwang, Imgon; Mazare, Anca Valentina; Schmuki, Patrik (Surface Science, 2022)
The insertion of cations such as H+ and Li+ to TiO2 photoelectrodes is a universally recognized method to enhance the electric conductivity of TiO2 electrodes. In the present work we report on the fabrication and use of Li+ inserted TiO2 nanotubes (NTs) as a photoanode scaffold in dye-sensitized solar cells (DSSCs). Li+ was successfully inserted into the TiO2 NTs by a cathodic treatment in 1 M LiClO4/ethylene carbonate (EC) electrolyte. We observe for DSSCs fabricated from such nanotubes an overall solar cell efficiency of ∼7.1% compared to an efficiency of ∼5.7% for the non Li-intercalated electrode. We ascribe this enhancement to a faster electron transport and an increased conductivity in the lithiated TiO2 NTs.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Anodization; Dye-sensitized solar cell (DSSC); Li ion intercalation; TiO